Performance of biodegradable microcapsules of poly(butylene succinate), poly(butylene succinate-co-adipate) and poly(butylene terephthalate-co-adipate) as drug encapsulation systems - Brunner, Cornelia T. (2011)
Poly(butylene succinate) (PBSu), poly(butylene succinate-co-adipate) (PBSA) and poly(butylene terephthalate-co-adipate) (PBTA) microcapsules were prepared by the double emulsion/solvent evaporation method. The effect of polymer and poly(vinyl alcohol) (PVA) concentration on the microcapsule morphologies, drug encapsulation efficiency (EE) and drug loading (DL) of bovine serum albumin (BSA) and all-trans retinoic acid (atRA) were all investigated. As a result, the sizes of PBSu, PBSA and PBTA microcapsules were increased significantly by varying polymer concentrations from 6 to 9%. atRA was encapsulated into the microcapsules with an high level of approximately 95% EE. The highest EE and DL of BSA were observed at 1% polymer concentration in values of 60 and 37%, respectively. 4% PVA was found as the optimum concentration and resulted in 75% EE and 14% DL of BSA. The BSA release from the capsules of PBSA was the longest, with 10% release in the first day and a steady release of 17% until the end of day 28. The release of atRA from PBSu microcapsules showed a zero-order profile for 2 weeks, keeping a steady release rate during 4 weeks with a 9% cumulative release. Similarly, the PBSA microcapsules showed a prolonged and a steady release of atRA during 6 weeks with 12% release. In the case of PBTA microcapsules, after a burst release of 10% in the first day, showed a parabolic release profile of atRA during 42 days, releasing 36% of atRA.